2013
DOI: 10.1017/s1743921313006418
|View full text |Cite
|
Sign up to set email alerts
|

How can star formation be sustained?

Abstract: Abstract. There is overwhelming evidence that the Milky Way has formed its stars at a relatively constant rate throughout the Hubble time. This implies that its stock of cold gas was not in place since the beginning but it has been acquired slowly through gas accretion. The gas accretion must have been at low metallicity in order to reconcile the metallicities observed in the disc with the predictions of chemical evolution models. But how does this gas accretion take place? I review the current evidence of gas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 87 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…The existence of HVCs agrees qualitatively with theoretical expectations; however, they pose an observational problem common to many other galaxies. Their mass infall rate is estimated to be ∼ 0.1-0.2 M year −1 which is one order of magnitude too small to maintain the MW SFR of ∼ 1-2 M year −1 (Sancisi et al 2008;Fraternali 2014), and thus inconsistent with the MW being in a stationary state sustained by HVCs (Sect. 2.1).…”
Section: Neutral Gas Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of HVCs agrees qualitatively with theoretical expectations; however, they pose an observational problem common to many other galaxies. Their mass infall rate is estimated to be ∼ 0.1-0.2 M year −1 which is one order of magnitude too small to maintain the MW SFR of ∼ 1-2 M year −1 (Sancisi et al 2008;Fraternali 2014), and thus inconsistent with the MW being in a stationary state sustained by HVCs (Sect. 2.1).…”
Section: Neutral Gas Observationsmentioning
confidence: 99%
“…The color coding shows the projected gas density in logarithmic scale, with the equivalence given in the inset. Densities are referred to the mean density of the universe at the time Silk and Mamon (2012), Combes (2014), Fraternali (2014), Conselice et al (2013) (observationally oriented), Shlosman (2013), Benson (2010) (theoretically oriented), and Madau and Dickinson (2014) (emphasizing the high-redshift aspects).…”
Section: Introductionmentioning
confidence: 99%
“…Oosterloo et al 2007) and the study of their kinematics (Fraternali 2009, and references therein) has revealed the interplay between the disc and the circumgalactic medium in late-type galaxies (Fraternali & Binney 2008;Marinacci et al 2010Marinacci et al , 2011. This interaction is mediated by a so-called galactic fountain (Shapiro & Field 1976;Houck & Bregman 1990) -which in the Milky Way manifests itself through intermediate-velocity (IVC) and high-velocity (HVC) clouds Marasco & Fraternali 2011;Wakker & van Woerden 1997;Wakker 2004) -and provided indi-rect evidence of how star formation can be sustained for a Hubble time in these systems (Fraternali 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The additional gas needed to support star formation can be provided by the IGM, feeding massive primeval galaxies via gas accretion through cosmic streams (Sancisi et al 2008;Fraternali 2014). Theoretical models and numerical simulation have thoroughly investigated the role of gas accretion in galaxy evolution.…”
Section: Introductionmentioning
confidence: 99%